Brain responses in infants - Hartley, C; Slater, R (Oxford University Press, 2021)
We cannot know whether another person is experiencing pain unless they tell us, making reliable pain assessment difficult in nonverbal infants. Consequently, the treatment of infant pain is reliant on inferences based on observations. Understanding how infants respond to noxious stimulation, and how their responses change with factors such as age, pathology, and sex, is essential to improve pain treatment and to evaluate the efficacy of pharmacological and nonpharmacological interventions. Even in the most immature infants, noxious stimulation evokes activity across all levels of the nervous system, eliciting changes in heart rate, respiratory rate, reflex withdrawal, hormonal responses, facial expression, and brain activity. This chapter focuses on measures of noxious-evoked brain activity in infants, including methods of assessment, use in clinical trials, and the current limitations of these techniques.